Anxiety disturbs the blood plasma metabolome in acute coronary syndrome patients - HongYan Wei (Nature Portfolio, 2021)
Abstract Coronary heart disease (CHD) is the result of a complex metabolic disorder caused by various environmental and genetic factors, and often has anxiety as a comorbidity. Rupture of atherosclerotic plaque in CHD patients can lead to acute coronary syndrome (ACS). Anxiety is a known independent risk factor for the adverse cardiovascular events and mortality in ACS, but it remains unclear how stress-induced anxiety behavior impacts their blood plasma metabolome and contributes to worsening of CHD. The present study aimed to determine the effect of anxiety on the plasma metabolome in ACS patients. After receiving ethical approval 26 ACS patients comorbid anxiety were recruited and matched 26 ACS patients. Blood plasma samples were collected from the patients and stored at − 80 °C until metabolome profiling. Metabolome analysis was performed by liquid chromatography mass spectrometry (LC–MS), and the data were subjected to multivariate analysis. Disturbance of 39 plasma metabolites was noted in the ACS with comorbid anxiety group compared to the ACS group. These disturbed metabolites were mainly involved in tryptophan metabolism, pyrimidine metabolism, glycerophospholipid metabolism, pentose phosphate pathway, and pentose and glucuronate interconversions. The most significantly affected pathway was tryptophan metabolism including the down-regulation of tryptophan and serotonin. Glycerophospholipids metabolism, pentose and glucuronate interconversions, and pentose phosphate pathway were also greatly affected. These results suggest that anxiety can disturb three translation of material in ACS patients. Besides the above metabolism pathways pyrimidine metabolism was significantly disturbed. Based on the present findings the plasma metabolites monitoring can be recommended and may be conducive to early biomarkers detection for personalized treatment anxiety in CHD patients in future.